(untitled) (Bangladesh Journal of Agricultural Research, 2026)
A study was conducted at the research field of Bangladesh Agricultural Research Institute (BARI), Gazipur to determine the optimum dose of N, P, K and S for higher seed yield of Gypsophila (Gypsophila paniculata). The experiment was designed with 15 treatment combinations taking 4 doses each of N (0, 70, 100 & 130 kg ha-1), P (0, 20, 40 & 60 kg ha-1), K (0, 60, 90 & 120 kg ha-1) and S (0, 10, 20 & 30 kg ha-1) arranged in a randomized complete block design (RCBD) with three replications. A blanket dose of 3 kg Zn ha-1 and 1.5 kg B ha-1 along with cowdung at 5 t ha-1 was used. The results showed that the significantly highest seed yield (903 kg ha-1) of gypsophila was recorded from combined application of 100 kg N, 40 kg P, 60 kg K and 20 kg S per ha which was 29% higher over control (N0P0K0S0).The maximum number of filled fruits per plant, seeds per fruit and 1000-seed weight were noted in the said treatment. The same treatment recorded the highest uptake of N, P, K and S. The apparent N, P and K recovery efficiency was also higher in the same treatment. The organic matter and total N in postharvest soil was also higher in the said treatment. The overall results suggest that combined application of N 100 kg, P 40 kg, K 60 kg and S 20 kg ha-1 including 3 kg Zn ha-1, 1.5 kg B ha-1 and 5 t ha-1 cowdung would help to increase seed yield of Gypsophila. Bangladesh J. Agril. Res. 47(4): 355-369, December 2022